Status of Soil Acidity under Different Land Use Types and Soil Depths: The Case of Hojje Watershed of Gomibora District, Hadiya Zone, Southern Ethiopia - Tesfaye Abure (Applied and Environmental Soil Science)
In the humid regions of Ethiopia, soil productivity and fertility are significantly affected by soil acidity, which is connected to infertility and mineral toxicity. The study aimed to assess the status of soil acidity under different land use types and soil depths in Hojje watershed of Gomibora district, Hadiya Zone, Southern Ethiopia, in November 1, 2020. Soil samples (24 nos.) were collected using X-design format from four different land use typeshome garden, cultivated land, grazing land, and Eucalyptus plantation at two soil depths (0–20 cm and 20–40 cm). The soil samples were prepared, their physiochemical characteristics were examined, and statistical analysis was performed. The results indicated that the soil under cultivated land and Eucalyptus plantation were strongly acidic (pH 5.15 and 5.32) with mean values of exchangeable acidity (4.6, 4.59 cmol(+) kg−1) and acid saturation percentage (47.85, 46.96%), respectively. The grazing land was moderately acidic (pH 5.63) and home garden soil was slightly acidic (pH 6.67). The home garden soils had statistically significant (p<0.01) lower exchangeable acidity (0.64 cmol(+) kg−1) and acid saturation percentage (2.61%). Although, soil pH (H2O and KCl), exchangeable acidity, acid saturation percentage, exchangeable base, CEC, and base saturation are significantly (p<0.01) affected by both the main effect and interaction effects of the two factors. As a result, it is advised to apply lime to the cultivated land to reduce the acidity of the soil for profitable crop production as the amount of acidity is above the tolerance limit for the area’s locally produced crops.